Peptides Associated with Bovine Thrombin Preparations - Landaburu, Ricardo H.; Harmison, Charles R.; Seegers, Walter H. (Thrombosis and Haemostasis, 1961)
When bovine thrombin was prepared by one method the N-terminal amino acid was glutamic acid while with another method it was threonine. In urea solution these N-terminal amino acids were removed in association with peptides and the N-terminal amino acid of the main protein was leucine. Urea treated thrombin had the same specific activity as the original from which it was prepared, and also had the same carbohydrate content. It was, however, less soluble in water and had a higher viscosity. The sedimentation constant was concentration dependent. Before treatment with urea the rate of change of the sedimentation constant with concentration was positive. After urea treatment it was negative. Extrapolation to zero concentration gave the same value for thrombin as for urea treated thrombin. The peptides removed from thrombin function to alter the properties of the protein. They are attached by bonds that are broken in urea solution. Very likely the original prothrombin molecule is, in part at least, composed of sub-units consisting of polypeptide chains held together by bonds broken by reagents such as sodium citrate. In addition to alanine, bovine prothrombin has arginine as N-terminal amino acid, but the latter was uncovered only in urea solution.